Designer Exosomes: Smart Nano-Communication Tools for Translational Medicine - Madhyastha Harishkumar (MDPI AG, 2021)
Exosomes are the master transporters of genes, RNAs, microRNAs, proteins, and lipids. They have applications in major diseases, including cancer, cardiovascular diseases, neurological disorders, and diabetes mellitus. Delivery of the exosomes to recipient cells is governed by the functional heterogenicity of the tissues. Engineered exosomes are promising tools in tissue regeneration. In addition to their role as intracellular communication cargos, exosomes are increasingly primed as standard biomarkers in the progression of diseases, thereby solving the diagnostic dilemma. Futuristic empowerment of exosomes with OMICS strategy can undoubtedly be a bio-tool in translational medicine. This review discusses the advent transformation of exosomes in regenerative medicine and limitations that are caveats to broader applications in clinical use.